FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP KONSUMEN MELALUI IKLAN TERHADAP KEPUTUSAN PEMBELIAN SPEEDY DI MAKASAR - AGUNG DWI NUGROHO (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
PT. Telkom is one of the telecommunications operator service providers and the information was well respected in the competitive telecommunications business in Indonesia, it is easy to understand because the company has moved and grown in advance in comparison with other operators, even a majority of shares are still owned by the government.This study focus on the product Speedy. Where the factors that influence consumer attitudes through advertising is included: the value of information, the contents of the message and boost advertising. Relating influence consumer attitudes through advertising on purchasing decisions Speedy, the researchers conducted a study on consumers because given this company has many customers and in addition the average consumer has an interest in purchasing the product speedy. From the research results as are the factors that influence consumer attitudes through advertising (the value of the information, content, advertisements encouragement) have a positive influence on consumer decision in purchasing Speedy in Makassar. It is based on test results F where F count> F table (51.73> 2.70). The independent variable (value information, message content, and boost advertising) that partially has the most dominant influence on the dependent variable (purchase decisions) is a variable value information. It is based on test results tcount> t table is 6.492> 1.985